Epistemic background of social ontology - Çağmar, Mehmet Şirin (Argumentos - Revista de Filosofia, 2025)
This article explores how epistemology plays a role within the realm of social ontology. My main claim is that every facet of the the social domain we deal with needs an epistemic framework and background in the construction of an ontology, contingent upon the fact that it has an ontological reality and existence. I think that two fundamentals make an significant contribution to this claim. The first of these is the notion of idea and its requisite foundation in social sphere, and the other is the concept concerning the common sense. Therefore, the initial part of this article centers on the treatment and examination of the the notion of the idea. My primary assertion in this section is to demonstrate that the concept of ide has a linguistic interconnection and that this connection needs a foundation within the social basis or context. In the subsequent fragment, where the concept of common sense is discussed, it is argued that common sense is a shared attribute among all individuals in common in the social field, and that it is emphasized that this shared common sense serves as an essential component making it possible to provide its epistemological foundations in the social context.